Design of rotatable direct energy deposition optical system - Choi, Byungjoo; Lee, Gwangjae; Lee, Kyuhang; Lee, Moon G.; Jeon, Yongho (Journal of Mechanical Science and Technology, 2019)
Currently, remanufacturing is actively conducted in the fields of automotive parts, toner cartridges, office furniture, and chemical catalysts. If parts involving large products and expensive materials are remanufactured, the consumption of resources and fossil fuels and the production of waste can be reduced. In the present study, a rotating compact optical system that can repair the inner wall of narrow cylinder parts by direct energy deposition (DED) was developed in head diameter within 60 mm. The development of the rotating optical system considers optics, internal flow, and mechanisms. The optical analysis, flow analysis, and mechanism design were systematically performed based on the design process of the opto-mechanical system. The results indicate that it is possible to perform rotating DED as confirmed by the deposition experiment.
Keywords: Beam profiles; Chemical catalyst; Deposition experiments; Energy depositions; Mechanism design; Office furniture; Opto-mechanical systems; Remanufacturing; Beam profile; Direct energy deposition; Flow simulation; Optical design; Remanufacturing; Rotatable optical system